Identification and characterization of probiotic yeast isolated from digestive tract of ducks. (11th July 2018) - Hu, X Q; Liu, Q; Hu, J P; Zhou, J J; Zhang, X; Peng, S Y; Peng, L J; Wang, X D
Abstract: The objective of this study was to isolate and identify yeast strains from the digestive tract of ducks, and evaluate in vitro their potential as probiotics in poultry. The yeast strains were isolated using malt extract agar medium, and identified through morphological, physiological, and biochemical tests as well as sequence homology analyses of 26S rDNA D1/D2 region. A total of 35 yeast strains were isolated from the guts of Cherry Valley meat ducks, including seven strains of Saccharomyces cerevisiae ( S. cerevisiae ). These seven strains of S. cerevisiae were further screened for their use as alternative yeast probiotics strains for poultry feed. The yeast strains were characterized for their cell surface hydrophobicity, autoaggregation ability, and resistance to high temperature (30°C, 37°C, and 42°C), low pH (2.0, 3.0, and 4.0), bile salts (0.3% and 0.6%), and nutrition starvation (2, 4, 6, 8, 10, and 12 days). The isolates of WHY-2 and WHY-7 had a higher survival percentage at 37°C, pH 2.0, 0.60% poultry bile salts, and 10 days of nutrition starvation, with higher cell surface hydrophobicity and autoaggregation, when compared with the other isolates, suggesting that the isolates WHY-2 and WHY-7, could be used as probiotic candidates. The data obtained in this study could help in selecting probiotic yeast candidates for use in poultry industry.